Factors Related To The Event Of Less Nutrition In Children Age 37-59 Months In The Center Of Public Health In Kaubele District Biboki Moenleu North Central Timor Regency - Elisabeth Usfal; Sugeng Maryanto; Indri Mulyasari (UNIVERSITAS NGUDI WALUYO, 2021)
Malnutrition problems in children under five can be influenced by energy intake, protein intake and the incidence of diarrhea. The purpose of the study was a factors associated with the incident of malnutrition in children aged 37-59 months at The Center Of Public Health Kaubele Moenleu Biboki District North Central Timor Regency.This study was a correlation descriptive study with a cross sectional approach. The sample consisted of 78 toddlers at the Kaubele The Center Of Public Health, Biboki Moenleu District, North Central Timor Regency, taken by proportional random sampling technique. Data collection instrument using secondary data from weighing results, kueisoner, form SFFQ. Data analysis using chi-square (Î± = 0.05). The result of this study indicated that there were intake energy good 8 toddlers ( 10.3 % ) , energy less 70 toddlers ( 89.7 % ); protein intake more 2 toddlers ( 2.6 % ) , protein good 32 toddlers ( 41.0 % ) , less 44 toddlers ( 56.4 % ); toddlers who do not diarrhea 36 toddlers ( 46.2 % ) , diarrhea 42 toddlers ( 53.8 % ); toddlers normal weight of 30 toddlers ( 38.5 % ) , toddlers weight less 48 toddlers ( 61.5 % ); There is correlation between intake energy , protein intake and the chain diarrhea with the genesis malnutrition in toddlers ( p = 0.025, p = 0.002 and p = 0.000 ). There is correlation between intake energy , protein intake and the chain diarrhea with the genesis malnutrition in toddlers 37-59 months in The Center Of Public Health Kaubele Biboki Moenleu District North Central Timor Regency.